Ability to Understand Mathematic Concepts: The Effect of The Hermeneutic Model Assisted by Gamification Teaching Materials - Sari, Juwita (Al-Khawarizmi, 2021)
The ability to understand mathematical concepts in learning mathematics needs to be mastered by students to support the learning process and solve various mathematical problems. This study aims to determine the effect of the Hermeneutics-Assisted learning model of gamification teaching materials on the ability to understand mathematical concepts of students. This research is a type of Quasy Experimental Design research with a 3×1 factorial research design. The data collection technique in this study was a test of the ability to understand mathematical concepts. The data analysis techniques used are normality test, homogeneity test, and one-way analysis of variance. Based on the results of the study, it was concluded that there was an effect of applying the Hermeneutics learning model assisted by gamification teaching materials on the ability to understand students' mathematical concepts. Hermeneutics learning model assisted by gamification teaching materials has a significant influence on the ability to understand mathematical concepts of students.